2010
DOI: 10.1017/s0031182009991867
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Apis mellifera workers by the parasitic mite Varroa destructor using host cuticular hydrocarbons

Abstract: The parasitic mite, Varroa destructor, is the most important threat for apiculture in most bee-keeping areas of the world. The mite is carried to the bee brood cell, where it reproduces, by a nurse bee; therefore the selection of the bee stage by the parasite could influence its reproductive success. This study investigates the role of the cuticular hydrocarbons of the European honeybee (Apis mellifera) in host-selection by the mite. Preliminary laboratory bioassays confirmed the preference of the varroa mite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 27 publications
4
49
0
Order By: Relevance
“…These results are consistent with those obtained when comparing the total time spent by the mite on the two bees (Z=-2.5, P=0.008; Z=-0.32, ns; Z=-0.55, ns, respectively). As the mite preference for bees performing different tasks is driven by a specific blend of cuticular hydrocarbons (CHCs) covering the body surface of nurses and foragers (Del Piccolo et al, 2010), we explored whether the chemical signature of nurses and foragers differed among individuals coming from colonies with different mite abundance. CHCs of nurses and foragers collected from three colonies with different mite abundance (no mites, 0.13 and 0.45) were extracted and analysed by gas chromatography coupled with mass spectrometry (GC-MS).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are consistent with those obtained when comparing the total time spent by the mite on the two bees (Z=-2.5, P=0.008; Z=-0.32, ns; Z=-0.55, ns, respectively). As the mite preference for bees performing different tasks is driven by a specific blend of cuticular hydrocarbons (CHCs) covering the body surface of nurses and foragers (Del Piccolo et al, 2010), we explored whether the chemical signature of nurses and foragers differed among individuals coming from colonies with different mite abundance. CHCs of nurses and foragers collected from three colonies with different mite abundance (no mites, 0.13 and 0.45) were extracted and analysed by gas chromatography coupled with mass spectrometry (GC-MS).…”
Section: Resultsmentioning
confidence: 99%
“…We tested this hypothesis by presenting phoretic mites (N=309) collected from eight hives (five out of the seven abovementioned colonies and three additional ones) with a binary choice between homocolonial and heterocolonial foragers. As mites are able to recognize different hydrocarbon blends on the bee cuticle (Del Piccolo et al, 2010), they may discriminate differences in the chemical signature among foragers belonging to different colonies. We found that 224 choosy mites [65 mites (21%) did not make any choice], regardless of the mite abundance of the colony, did not show nestmate host recognition ability (G=4.84, d.f.=2, ns) or, at least, they did not express it in our experimental setup (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Carlson and Bolton, 1984), nestmate recognition (Dani et al, 2005) and elucidation of host-parasite relationships (Rickli et al, 1994;Salvy et al, 2001;Del Piccolo et al, 2010). (Blomquist et al, 1980;Francis et al, 1985;Francis et al, 1989;Carlson et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Brood food contains a volatile compound, 2-hydroxyhexanoic acid 24 (enantiomer not known), that is attractive to phoretic Varroa females (Nazzi et al 2004). Finally, foragers appear to have higher titers of (Z )-8-heptadecene 25 in their cuticular hydrocarbon blend than nurses, and this compound has been also shown to deter Varroa females (Piccolo et al 2010).…”
mentioning
confidence: 96%